Assessment of Forty-Five Bambara Groundnut (Vigna subterranea) Accessions Under Varying Environments in Kenya Using Morphological and Yield Components - Mercy Chelangat; Bernard M. Gichimu; Phyllis W. Muturi; Josiah N. Gitari (International Journal of Agronomy)
Understanding the agromorphological diversity of Bambara groundnut is crucial in enhancing its adaptability and productivity in Kenya, where production is localized to a few areas. Owing to its agronomic and nutritional benefits, it has been deemed prudent to introduce this high-value crop to other growing areas. This will require identification of genotypes with superior agronomic and end-user traits for the areas being considered. The objective of this study was to determine the agromorphological diversity of Bambara groundnut accessions under varying ex situ environmental conditions in Kenya. For two cropping seasons, field experiments were conducted in three different agroecological sites in Embu County, namely, Kangaru, Kiamuringa, and Ishiara. The experiments were laid out in a randomized complete block design (RCBD) with 45 accessions in each location replicated three times. There were significant differences (p<0.05) in all the agromorphological variables except days to flowering and plant height. Grain yields ranged from 0.80 to 2.74 t ha−1 in accession BS-132 and BS-107, respectively. The accessions were grouped into five distinct clusters depicting high morphological diversity. Significant correlations were observed between some phenological parameters and yield components. The accessions BS-107, LU-122, LU-121, BS-134, and BS-144 were identified among the higher yielders and recommended for adoption within the tested and similar agroecological conditions. The GGE biplot patterns of mean performance and stability indicated that, for yield, BS-144 and KS-116 and the accessions plotted near them are considered ideal and desirable.